Lowriders in space. Book 1 - Camper, Cathy (Chronicle Books, 2014)
Friends Lupe Impala, El Chavo Flapjack, and Elirio Malaria share a love of fixing up cars, and enter a contest to fix up a lowrider with the hopes of winning a cash prize that will enable them to open their own shop. Includes Spanish words and phrases with translations throughout the text.